Effect of the inner diameter and Reynolds number on the recirculation zone in annular jet flow - Merouane, Habib; Sahnoun, Rachid; Drai, Ismail (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we focus on the effect of the inner diameter and Reynolds number on the recirculation zone in an annular jet flow with numerical simulation by resolving the Reynolds-averaged Navier-Stokes equations with the first closed model of turbulence k-epsilon. The annular jet plays an essential role in stabilizing the flame in the burner which is used in many industrial applications.
Keywords: jet flow; annular jet; recirculation zone